Study of factors affecting the energy consumption of the mixing plant for the preparation of aerated concrete - Vasiliev, Oleksii; Kulai, Volodymyr (Academic journal Industrial Machine Building Civil Engineering, 2025)
The current stage of development of the construction industry is characterized by increased requirements for the energy efficiency of technological processes and the quality of building materials. The preparation of aerated concrete is a complex technological process and its efficiency is largely determined by the mixer’s operating parameters. One of the key indicators that affects both the quality of the finished mixture and the cost-effectiveness of the process is the energy consumption of the mixing plant. The article presents the results of a study of the influence of the main technological and design parameters on the energy consumption of the mixing plant for preparing aerated concrete. The purpose of these measurements was to determine the patterns of changes in the mixer’s electricity consumption depending on the frequency of rotation of the working body, the duration of mixing and the mobility of the concrete mixture. To achieve this goal, mathematical planning methods were used, namely a three-factor experiment of the second order, thanks to which a mathematical model of the electricity consumption of the plant for preparing aerated concrete was obtained in the form of a regression equation. The developed model allows us to estimate the magnitude of the individual impact of each factor on energy consumption and determine their optimal range. Based on the data, graphical dependencies were constructed that reflect the change in the energy consumption of the plant. The results of the study show that the decisive influence on the energy efficiency of the process is the frequency of rotation of the working body and the fluidity of the mixture, while the rational duration of mixing is about 40 seconds. The study creates the prerequisites for optimizing the energy consumption of mixing equipment and improving the quality of the preparation of aerated concrete in mobile forced-action plants.